2007
DOI: 10.1149/1.2780937
|View full text |Cite
|
Sign up to set email alerts
|

New Platinum-Free Carbon Nitride Electrocatalysts for PEMFCs Prepared Using as Precursors PAN/M(CNCH3)x Complexes (M = Pd, Co, Au, Ni)

Abstract: A new synthesis protocol aimed at the preparation of palladium-based, platinum-free carbon nitride electroctatalysts for PEMFCs is described. First, a metallorganic precursor is prepared by coordinating metal complexes with a nitrogen-ligand macromolecule; second, a suitable thermal treatment is applied to the precursor to obtain the final electrocatalyst materials. This protocol allows to prepare materials having a well-controlled chemical composition and including in their structure a significant amount of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…This evidence has been attributed to an incomplete reduction of the anionic metal complexes used in the synthesis; the potassium atoms are needed to counterbalance their electrical charge. A similar behaviour has already been observed in other systems prepared with the same protocol (11)(12)(13)(14)(15)(16)(17)(18). A small percentage of nitrogen, provided by the -C≡N groups of the reagents, has also been detected confirming the formation of a carbon nitride-based support.…”
Section: Chemical Compositionsupporting
confidence: 83%
See 2 more Smart Citations
“…This evidence has been attributed to an incomplete reduction of the anionic metal complexes used in the synthesis; the potassium atoms are needed to counterbalance their electrical charge. A similar behaviour has already been observed in other systems prepared with the same protocol (11)(12)(13)(14)(15)(16)(17)(18). A small percentage of nitrogen, provided by the -C≡N groups of the reagents, has also been detected confirming the formation of a carbon nitride-based support.…”
Section: Chemical Compositionsupporting
confidence: 83%
“…Indeed, it is expected that the best ORR performance can be achieved only if the "active metal" is free of adsorbates and in its (0) oxidation state (15,17). Fe plays a crucial role in the desorption process of the intermediates from the neighboring active sites of Pd, thus enhancing the turnover frequency of the electrochemical process and allowing the ORR to be carried out with a larger fraction of active sites covered by oxygen species (13)(14)(15)(16)(17)(18). This latter phenomenon is confirmed by the low value of the observed Tafel slope.…”
Section: Electrochemical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, nitrogen atoms in PdCoNi-CN l 900/G material are provided by the -CN groups of the K 2 Ni(CN) 4 ·xH 2 O and K 3 Co(CN) 6 reagents; this preparation protocol results in a very small weight fraction nitrogen in the precursor. Nitrogen atoms are expected to be present on the support matrix hybridized either sp 2 or sp 3 (12,19) No hydrogen atoms have been detected in the chemical composition of the materials. This suggests that the graphitization of the carbon nitride matrix was complete, thus leading to supported electrocatalysts with a very good electrical conductivity.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…In this way, the Tafel plots in the ORR process of the electrocatalysts assembled in a real MEA were obtained and reported in Figure 8 The data shown in Figure 8 are consistent with those obtained with "ex-situ" measurements applying the CV-TF-RRDE method (see Figure 5). It is observed that the reaction mechanism in the ORR process for the various materials follows a 4-electron pathway and that in this potential region the surface of all electrocatalysts is covered by an oxide layer which hinders the adsorption of O 2 molecules as witnessed by the magnitude of the Tafel slope (~60 mV/decade) (11,12,17,18,22). In comparison with the platinum-based EC-20 electrocatalyst, the PdCoNi-CN x 900/G materials exhibit an overpotential higher by 70 and 100 mV for x = l and h, respectively.…”
Section: Tests In a Single Cell Configurationmentioning
confidence: 99%